Theorizing Small Towns in Anthropological Views in Nepal - Bhatta, Badri Nath (Tribhuvan University Journal, 2018)
This paper has attempted to define the terms urban, urbanism, cities and towns which are confusing terms however interrelated. An interdisciplinary approach has been adopted to achieve this objective. The towns are small in size, population along with development basis than cities. Earlier stage of towns or small towns was village. As a foundation, village was the original form of all. In this sense, it is focused on the overall urban−rural structure where rural/village has crucial role to develop town to cities. Archeologically, the effort to subsist in primitive people was based on the process of agricultural farming. The first and early civilization in human behaviours was found in Near East (similar as Middle East in West Asia) as initial town at the bank of the river. Therefore, the origin of the towns indicates early people began to be civilized in their daily activities. Later, the towns were extended. In Nepal, there are generally urban areas, cities, towns and villages as local levels in the forms of Metropolitan Cities, Sub Metropolitan Cities, Municipality, and Rural Municipality at the one side, DUD BC at the other has classified into five classes− metro city, sub- metro city, city, sub-city or small town and urban centre based on urban faculties and population.